Surgical Dilemmas Associated with Malignant Large Bowel Obstructions - Schwartzberg, David M.; Valente, Michael A. (Clinics in Colon and Rectal Surgery, 2022)
Despite an increase in screening colonoscopy, with the objective to decrease the incidence of colorectal cancer, a third of patients will present with an obstructing cancer. Malignant large bowel obstructions (MLBO) pose a challenging workup and treatment paradigm where an oncologic primary tumor resection must be balanced with relieving the obstruction, functional outcomes, palliation, and consideration for adjuvant therapy. A thorough work up with cross-sectional imaging and medical optimization should be attempted; however, patients may present in extremis and require emergent intervention. The onset of MLBO can be insidious, but result in electrolyte derangements, perforation, small bowel obstruction, hemorrhage, and ischemia. Self-expandable metallic stents have been used as palliation or as a bridge to surgery and have allowed for minimally invasive surgical options as well as a decrease in stoma rates. Patients with signs of colon ischemia or perforation require emergent surgery, which is associated with an increase in stoma formation, morbidity, mortality, and a decrease in overall survival.
Keywords: colon cancer; rectal cancer; obstructing colorectal cancer; malignant bowel obstruction; large bowel obstruction; endoluminal stent